When Military Uniforms Change into Prison Uniforms: Military Prison Incarceration Among Ethiopian Soldiers in the Israel Defense Forces - Itzik, Lea (Criminal justice and behavior, 2023)
In contrast with studies examining the incarceration experience in civil prisons, there is a lack of literature and theory focusing on the military prison incarceration experience. The present retrospective qualitative study explored the experience of 27 Ethiopian-Israelis, an overrepresented population in Israeli military prison, incarcerated during their military service due to desertion offenses. Two main themes developed from the interviews: (a) the military prison as a tool to achieve personal goals and (b) Self-perception as victims of the system. Findings suggest that military prison incarceration may be a different experience to that of civilian incarceration, at times lacking the negative psychological described in literature on civil incarceration. On a theoretical level, results suggest that the incarceration experience may not be universal but, rather, dependent on the social and cultural context and meaning of the incarceration for the individual involved.